Study on multi-subject behavior game of CCUS cooperative alliance - Song, Xiaohua; Ge, Zeqi; Zhang, Wen; Wang, Zidong; Huang, Yamin; Liu, Hong (Energy (Oxford), 2023)
As a carbon reduction technology, CCUS (Carbon Capture, Utilization and Storage) is an important way to achieve the goal of “carbon peak and carbon neutrality” in China. In order to change the situation of slow commercialization and large-scale development of CCUS, this paper proposes to establish a CCUS cooperative alliance. Taking alliance organizers, institutional investors, upstream operators and downstream operators as research objects, the evolutionary game model is developed to reveal the dynamic evolution mechanism of CCUS cooperative alliance and analyze the impact of exogenous variables on the strategic choices of alliance members. The results show that: (1) establishing a strong market-oriented alliance can promote the large-scale deployment and commercialization of CCUS, (2) when return on investment is greater than or equal to 6%, it can effectively promote the investment of institutional investors in CCUS field, (3) when the government subsidy rate is greater than or equal to 75%, the willingness of downstream operators to operate independently is significantly enhanced. This study reveals the operation mechanism of the alliance, provides theoretical and methodological support for the operation and management of the alliance, and is of great significance to promote the cooperative operation and development of the alliance. •A CCUS cooperative alliance with commercial characteristics is proposed.•An evolutionary game model is developed to reveal evolution mechanism of alliance.•ROI of 6% or more can promote institutional investors' investment in CCUS.•Subsidy rate of 75% or more can urge downstream operators to operate independently.